Association of High Sensitivity C-reactive Protein in Acute Ischemic Stroke (Bangladesh Journal of Neuroscience, 2026)
Objectives: Stroke causes 9% of all deaths around the world and it remains the second common cause of death. Around 85% cases, the cause of stroke proved to be ischemic in which atherosclerosis is the pathogenic mechanism. Recent studies have shown that high sensitivity CRP (hsCRP) is a risk factor for ischemic stroke. Aims: To evaluate the association of hsCRP with acute ischemic stroke in Bangladeshi patients.Methods: This case control study was carried out from June 2011 to November 2011 in the department of Neurology, Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM) General Hospital, Dhaka in all the OPD and admitted stroke patients meeting the inclusion criteria. Serum hsCRP level was assessed in all stroke patients and controls.Results: Mean value of hsCRP among cases was 4.01(SD±2.61) mg/L and among controls was 1.65(SD±1.41) mg/L which was highly significant (p value